Multiple Ecological Parameters Affect Living Benthic Foraminifera in the River-Influenced West-Central Bay of Bengal - Suokhrie, Thejasino; Saraswat, Rajeev; Nigam, Rajiv (Frontiers in Marine Science, 2021)
The huge riverine influx and associated processes decrease the ambient salinity, stratify the water column, modulate the oxygen-deficient zone, and are also responsible for the recent acidification in the Bay of Bengal. Here, we have studied the effect of these riverine influx-dominated ecological parameters on living benthic foraminifera in the west-central Bay of Bengal. We report that the pH below 7.6 in front of the Krishna river, reduces the diversity and the richness of living benthic foraminifera on the adjacent shelf and the slope. A similar decreased diversity and richness is also observed in front of the Godavari River. We delineate three prominent assemblages, representing different depth zones with associated distinct physico-chemical conditions. The shallow water assemblage (∼27–100 m) is represented by Nonionella labradorica, Hanzawaia nipponica, Brizalina dilatata, Ammonia tepida, and Nonionella limbato-striata. These species are adapted to relatively warmer temperatures and more oxygenated waters. The deepwater assemblage (∼1,940–2,494 m) includes Bulimina cf. delreyensis, Bulimina marginata, Hormosinella guttifera, Cassidulina laevigata, and Gyroidinoides subzelandica and can tolerate a relatively colder temperature. The intermediate-depth assemblage (∼145–1,500 m) dominated by Eubuliminella exilis, Bolivinellina earlandi, Fursenkoina spinosa, Bolivinellina lucidopunctata, Globobulimina globosa, Fursenkoina spinosa, Eubuliminella cassandrae, Uvigerina peregrina, Rotaliatinopsis semiinvoluta, and Cassidulina laevigata, represents oxygen-deficient and organic carbon-rich environment. Besides the pH, temperature, dissolved oxygen and organic matter, we also report a strong influence of bathymetry, coarse fraction (CF) and the type of organic matter on a few living benthic foraminifera. The ecological preferences of 40 such dominant living benthic foraminifera, each representing a specific environment, have also been reported for site-specific proxy. We conclude that although the huge riverine influx affects living benthic foraminifera on the shelf, the dissolved oxygen and organic carbon mostly control benthic foraminiferal distribution in the deeper west-central Bay of Bengal.